2018
DOI: 10.1111/ppa.12953
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma species associated with green mould disease of Pleurotus ostreatus and their sensitivity to prochloraz

Abstract: Green mould disease causes serious economic losses in Pleurotus ostreatus crops worldwide, including in Italy, where prochloraz is the only chemical fungicide allowed to control the disease. The effectiveness of the doses 0.01, 0.05, 0.25 and 1.25 μL L−1 (field dose) of prochloraz (Sponix Flow, 450 g L−1), against colony growth rate and spore germination of Trichoderma pleuroti, T. pleuroticola and T. guizhouense strains on wheat straw extract agar plates were evaluated. Complete inhibition of Trichoderma pleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 27 publications
4
34
0
1
Order By: Relevance
“…Several studies have confirmed that species in this clade are important because of their mycoparasitism ( Chaverri et al 2015 ; Chen and Zhuang 2017a ; Sun et al 2019). When numerous biological control agents were explored deriving from species in the Harzianum clade ( Chaverri et al 2015 , several taxa, such as T. atrobrunneum T. pleuroti , and T. pleuroticola were recognized as causing agents of “Green mold” disease of cultivated mushroom ( Innocenti et al 2019 ; Sun et al 2019a , b ). In this study, T. lentinulae was isolated from a fruiting body and the cultivated substrates of L. edodes , causing the decay of the host as well.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have confirmed that species in this clade are important because of their mycoparasitism ( Chaverri et al 2015 ; Chen and Zhuang 2017a ; Sun et al 2019). When numerous biological control agents were explored deriving from species in the Harzianum clade ( Chaverri et al 2015 , several taxa, such as T. atrobrunneum T. pleuroti , and T. pleuroticola were recognized as causing agents of “Green mold” disease of cultivated mushroom ( Innocenti et al 2019 ; Sun et al 2019a , b ). In this study, T. lentinulae was isolated from a fruiting body and the cultivated substrates of L. edodes , causing the decay of the host as well.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary BLAST searches with ITS , RPB2 , and TEF1-α gene sequences of the new isolates against NCBI, TrichOKey (Druzhinina and Kopchinski 2006), and TrichoBlast ( Kopchinskiy et al 2005 ) databases identified species closely related to our isolates. Based on this information, sequences of ITS , RBP2 , and TEF1-α of 133 strains, representing 59 species were downloaded from GenBank, following recent publications ( Qin and Zhuang 2017 ; Qiao et al 2018 ; Innocenti et al 2019 ). Among them, 139 strains are belonging to the Harzianum clade, and Trichoderma ceramicum , T. parestonicum , and T. estonicum were chosen to represent the outgroup.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations